Projective variability of (semi)factive verbs in family of sentence contexts: A rating study - Sieker, Judith; Solstad, Torgrim (Proceedings of the Amsterdam Colloquium, 2022)
Investigating the influence of the embedding context on the projectivity of factive and semifactive predicates, this study has two main goals. On the one hand, we investigate empirically whether factive and semifactive verbs exhibit different degrees of projectivity depending on the Family of Sentences context in which they are embedded (as claimed by Karttunen [9]). Furthermore, we also investigate the relationship between projectivity and at-issueness for these contexts, thereby offering new experimental evidence regarding the Gradient Projection Principle (as formulated by Tonhauser et al. 2018 [23]). The results from our web-based rating study in German show two things: First, our study provides new empirical evidence that the Gradient Projection Principle does indeed generalize to the other Family of Sentences contexts. Second, our results do not support [9]’s theoretical claim as to the influence of the embedding context on projectivity for these verbs. Still, the data provide new empirical support for the observation that the individual verbs do differ with regard to their projectivity, beyond their partition along the lines of (semi)factivity.